The crisis as a scenario for the emergence of social entrepreneurship: the case of the Universidad del Valle - Rodríguez-Ramírez, Alfonso; Zapata-Domínguez, Alvaro (Sociedad y Economía, 2020)
The purpose of this paper is to describe the influence of the environment in the historical evolution of the Universidad del Valle, especially in the years 1962 – 1995 of economic and social crisis, which served as a scenario for social entrepreneurship, led by professors and workers. These environments discovered specific social, economic, political and cultural aspects, which influenced the behavior of community leaders inside the University in order to create social enterprises with services of health, education, social well-being, savings and credit, which the University could not finance. It was applied a methodology of content analysis, identifying facts that showed difficulties for the University to finance its functioning and investment. The period 1962 – 1995 was identified because, in that time, 15 social enterprises of solidarity economy were established, which moderated the impact of the crisis and give alternatives of solution to the problems of the Universidad del Valle financing.